Desenvolvimento de um goniômetro indutivo com bobinas ortogonais para aplicações biomédicas - Turqueti, Carlos Augusto D'Orazio (2017)
This dissertation describes the development of an inductive goniometer for the measurement of joint angle. The goniometer aims to measure angles up to 360 ° and the possibility of measurement in joints with more than one degree of freedom. For this it uses as base the work of Laskoski (2010) and aeronautical navigation systems. The experiment performed by Laskoski (2010) makes measurements up to 180 ° and the coils need to be aligned. The systems used in aeronautical navigations use the electronic compass and the automatic direction finder, that systems work with magnitudes in the order of kilometers. This experiment aims to adapt the navigation systems using the magnetic field to be able to measure angles at small distances. The tests were satisfactory comparing the errors found with the results of the experiments of Laskoski (2010) and Carbonaro et al. (2014). The maximum error over a distance of 7.5 cm is 10.6 ° and the misalignment between the coils of + 20 ° and -20 ° generates an error of at most 1.71 °.